Hygienic, Pathological and Economic Impacts of Liver Lesions at some Slaughterhouses in Suez Canal Region, Egypt - Ahmed, Nada I. H.; Ahmed, Ali Meawad; Abdel-Wahab, Mariam Ahmed (Journal of Advanced Veterinary Research, 2023)
Liver is budget-friendly and full of nutrients including protein, and micronutrients as vitamin B12, vitamin A, riboflavin, copper, and iron. Liver appeared as the most affected organ among offal of slaughtered animals. This work had studied the pathological lesions in a total of 85200 different slaughtered animals in many providence abattoirs in Suez Canal region through year 2021. The direct economic loss from organs condemnation (Kg) was also assessed. In 2021, a total of 4200, 64800 and 16200 camels, cattle, and sheep respectively were slaughtered for domestic consumption. The percent of liver lesions from camels, cattle, and sheep were 1.04%, 3.62%, and 2.85 respectively. The total economic losses due to the liver condemnation of camel, cattle and sheep were 31680 LE (2023 $), 1313760 LE (83893 $) and 138600 LE (8851 $) respectively. The total economic loss due to liver condemnation reached 1484040 LE (94766 $). The results of the current study made clear the need for the creation of an efficient program to combat Egypt's meat-related social problems.